2021
DOI: 10.1080/21655979.2021.2006863
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA HOTAIR promotes bone marrow mesenchymal stem cell differentiation by sponging microRNA miR-378g that inhibits nicotinamide N-methyltransferase

Abstract: Osteoporosis (OP) is associated with a serious social and economic burden. Recent studies have shown that the differential expression of long non-coding RNAs (lncRNAs) is closely related to OP. However, the specific molecular mechanism of HOX transcript antisense intergenic RNA (HOTAIR) remains to be elucidated. The expression of HOTAIR and miR-378g in OP patients was detected using quantitative reverse transcription polymerase chain reaction (qRT-PCR). Bone marrow mesenchymal stem cells (BMSCs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Bioinformatic analyses conducted in the current study preliminarily predicted that miR-378g is a miRNA directly targeted by PAX8-AS1. A previous study has confirmed that miR-378g promotes the osteogenic differentiation of bone marrow mesenchymal stem cells after escaping from the inhibition caused by HOTAIR [ 27 ]. HOTAIR confers ADM resistance in AML [ 13 ].…”
Section: Introductionmentioning
confidence: 93%
“…Bioinformatic analyses conducted in the current study preliminarily predicted that miR-378g is a miRNA directly targeted by PAX8-AS1. A previous study has confirmed that miR-378g promotes the osteogenic differentiation of bone marrow mesenchymal stem cells after escaping from the inhibition caused by HOTAIR [ 27 ]. HOTAIR confers ADM resistance in AML [ 13 ].…”
Section: Introductionmentioning
confidence: 93%
“…Patients with the HOTAIR rs7958904 CC genotype had significantly lower CD19 levels than patients with the HOTAIR rs7958904 GG and GC genotypes ( p = 0.032; Table S7 , Figure S1 ). Abnormal HOTAIR expression has also been reported in development of various diseases [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs are small noncoding RNAs that regulate gene expression via recognition of cognate sequences and interference of transcriptional, translational or epigenetic processes ( Chen L. et al, 2019 ), miRNAs control mRNA expression, miRNAs are also capable of targeting non-coding RNAs, including long non-coding RNAs and miRNAs ( Hill and Tran, 2021 ). Recently Yu et al ( Yu et al, 2021 ) and Wang et al ( Wang et al, 2021 ) identified miR-29b-3p and miR-378g as potential miRNAs upstream of NNMT by bioinformatics analysis. It was confirmed by dual luciferase reporter assay that miR-29b-3p and miR-378g directly target the 3′UTR of NNMT and negatively regulate NNMT expression.…”
Section: Nnmt As a Therapeutic Target For Metsmentioning
confidence: 99%